Influence of Vitrectomy-related Factors on the Outcome of Ahmed Glaucoma Valve Implantation - Jo, Jaehyuck (Korean J Ophthalmol, 2018)
PURPOSE: To evaluate the outcome of Ahmed glaucoma valve (AGV) implantation in eyes with refractory secondary glaucoma following pars plana vitrectomy (PPV) and the associated prognostic factors. METHODS: A total of 146 eyes in 146 patients who underwent AGV implantation after PPV (followed up for ≥1 year) were included. AGV implantation was considered successful when the intraocular pressure (IOP) was 6 to 21 mmHg regardless of using IOP-lowering medication. The hazard ratios (HRs) associated with surgical failure were determined with Cox proportional analysis. RESULTS: The most common cause for PPV was complications of proliferative diabetic retinopathy (50%). The mean and peak IOPs between PPV and AGV implantation were 26.9 ± 6.6 and 35.9 ± 10.2 mmHg, respectively. AGV implantation was performed on average 18.7 months after PPV, and its overall success rate was 80.1% during a mean follow-up period of 43.6 months. In multivariate analyses, rubeosis observed before AGV implantation (HR, 4.07; 95% confidence interval, 1.57 to 10.6; p = 0.004) and higher peak IOP before AGV (HR, 1.04; 95% confidence interval, 1.00 to 1.07; p = 0.034) were predictive of failure. However, no PPV-related factors were associated with the surgical outcome of AGV implantation. CONCLUSIONS: The outcome of AGV implantation is good in refractory glaucoma following PPV. Rubeosis after PPV and higher peak IOP before AGV are risk factors for poor outcomes. Patients who undergo PPV should be followed for the development of rubeosis and IOP control.